Photocatalytic Degradation of Lignin using TiO2 from Ilmenite Prepared by Microwave Method - Irwan, Irwan; Maindi, Andri Jahir; Edihar, Muh; Nurdin, Muhammad; Salim, La Ode Agus (Asian Journal of Environmental Research, 2024)
This study investigates the photocatalytic degradation of lignin using TiO2 extracted from ilmenite through a microwave-assisted method. Characterization of the iron sand, which serves as the source of ilmenite, was conducted using X-ray fluorescence spectroscopy (XRF) and Energy Dispersive X-ray Spectroscopy (EDX). The XRF analysis revealed that the iron sand primarily consists of Fe and TiO2, with minor impurities such as Al2O3, MgO, and SiO2. After extraction, the iron mineral content increased significantly, while impurities decreased. EDX analysis confirmed the presence of Fe, O, and Ti elements in the iron sand sample, originating from various iron oxide phases. Subsequent degradation tests on lignin with varying microwave heating durations of ilmenite showed that a 90-minute heating duration achieved the highest lignin degradation percentage of 56.69%. This suggests that the optimum heating time for ilmenite is crucial for maximizing its photocatalytic activity. Overall, the findings highlight the potential of microwave-prepared TiO2 from ilmenite for efficient lignin degradation, with implications for environmental remediation and industrial applications.